FAM20C regulates osteoblast behaviors and intracellular signaling pathways in a cell‐autonomous manner. Issue 4 (27th October 2017) - Liu, Chao; Zhang, Hua; Jani, Priyam; Wang, Xiaofang; Lu, Yongbo; Li, Nan; Xiao, Jing; Qin, Chunlin
Abstract : Recent studies indicate that Family with sequence similarity 20 member C (FAM20C) catalyzes the phosphorylation of secreted proteins, and participates in a variety of biological processes, including cell proliferation, migration, mineralization, and phosphate homeostasis. To explore the local influences of FAM20C on osteoblast, Fam20c ‐deficient osteoblasts were generated by treating the immortalized Fam20c f/f osteoblasts with CMV‐Cre‐IRES‐EGFP lentivirus. Compared with the normal Fam20c f/f osteoblasts, the expression of Bone sialoprotein ( Bsp), Osteocalcin ( Ocn), Fibroblast growth factor 23 ( Fgf23), and transcription factors that promote osteoblast maturation were up‐regulated in the Fam20c ‐deficient osteoblasts. In contrast, the expression of Dental matrix protein 1 (Dmp1), Dentin sialophosphoprotein (Dspp), Osteopontin (Opn), type I Collagen a 1 (Col1a1), and Alkine phosphatase (Alp) were down‐regulated in the Fam20c ‐deficient cells. These alterations disclosed the primary regulation of Fam20c on gene expression. The Fam20c ‐deficient osteoblasts showed a remarkable reduction in the ability of forming mineralized nodules. However, supplements of extracellular matrix proteins extracted from the normal bone failed to rescue the reduced mineralization, suggesting that FAM20C may affect the biomineralization by the means more than local phosphorylation of extracellular matrix proteins and systemic phosphorus homeostasis. Moreover, although Fam20c deficiency had little impact on cell proliferation, it significantly reduced cell migration and lowered the levels of p‐Smad1/5/8, p‐Erk and p‐p38, suggesting that the kinase activity of FAM20C might be essential to cell mobility and the activity of BMP ligands. In summary, these findings provide evidences that FAM20C may regulate osteoblast maturation, migration, mineralization, and BMP signaling pathways in a cell‐autonomous manner. Abstract : As a kinase for the phosphorylation secreted proteins, Fam20c plays a role in bone and tooth mineralziation by regulating systemic phosphorus homeostasis. Additionally, Fam20c can also directly regulate the osteoblast behavior, gene expression and signaling pathway in a cell autonomous manner, which may work through the phosphorylation of BMP ligands.